Desarda’s versus Lichtenstein technique of inguinal hernia repair - Syed, Obaid (International Surgery Journal, 2017)
Background: Ideal method for modern hernia surgery should be simple, cost effective, safe, tension free and permanent. The Lichtenstein operation to a great extent achieves this entire goal. The Lichtenstein mesh repair is associated with complications, postoperative dysfunction and high cost composite meshes. Desarda's technique, became a new surgical option for tissue-based inguinal hernia repair. The present study was designed to evaluate and compare the effectiveness and complications of the Desarda’s repair with Lichtenstein tension-free mesh repair for treatment of inguinal hernia in a developing country. Methods: 200 patients with unilateral, primary, reducible inguinal hernia were selected. Included patients were randomly divided into two groups. Studied parameters were Duration of surgery, intra operative complications, post-operative Pain, Duration of hospital stay, return to normal activities, post-operative complications and recurrences. Results: There were a total of 100 patients each group. There was no statistically significant difference in duration of surgery and complication rate between the two groups. Difference in mean VAS was not statistically significant. The mean hospital stay in Desarda’s technique was 2.5 days while it was 2.6 days in Lichtenstein’s group. The mean time to return to basic physical activity in the Desarda’s technique was 12.6 days while it was 13.3 days in the Lichtenstein’s group. There were no recurrences in either group. Chronic inguinal pain (>1month) was more frequent in Lichtenstein’s group. Conclusions: There is no significant difference in duration of surgery, intra operative complication rate, post-operative pain, complications and recurrence, between Desarda’s technique and Lichtenstein’s technique. However chronic inguinal pain is less in Desarda’s technique. Desarda’s repair must be considered in young patients (<30 years). Its long-term efficacy needs to be studied with larger, prospective double-blind randomized trials, with longer follow-up.